Behavior of mothers and teachers in providing education on menstrual hygiene to adolescent girls with autism spectrum disorder (ASD) - Girsang, Ruth Roselin; Prabandari, Yayi Suryo; Ratrikaningtyas, Prima Dhewi (BKM Public Health and Community Medicine, 2021)
Purpose: Persons with disabilities are divided into four categories: persons with physical, intellectual, mental, and sensory disabilities. Social and communication dysfunctions are symptoms of an autism spectrum disorder (ASD). This study aims to explore the methods used by mothers and school teachers in providing menstrual hygiene education to adolescent girls with ASD. Methods: This research consists of two steps: a systematic review using meta-synthesis, and a qualitative approach through semi-structured interviews conducted with participants at two different locations in D.I. Yogyakarta. Results: The combination of the two methods obtained: 1) Communication and education. Categories: mother-child relationships, and modes of communication with ASD; 2) The role of mothers and teachers; 3) Obstacles encountered. Categories: communication, rejection, and mother’s feelings; 4) Mother’s worries. Categories: children’s independence, interactions with friends, and the child’s future. Conclusion: Mothers and teachers provide menstrual hygiene information through early introduction, continuous repetition, associating words with relevant concepts, and using electronic media as an educational tool.